ChemInform Abstract: Activities of Heterogeneous Acid—Base Catalysts for Fragrances Synthesis. Issue 37 (22nd August 2013) - Hartati, H.; Santoso, Mardi; Triwahyono, Sugeng; Prasetyoko, Didik
Abstract Review: 38 refs.